Differential Movement Synchronous Tracking Control Strategy of Double-Shaking Table System Loading with Specimen - Xiaojun Li; Juke Wang; Fangfang Li; Na Li; Haohua Huang (Shock and Vibration)
Multisupport, multidimension, and nonuniform excitation seismic experiments have new requirements for shaking table array system in synchronous tracking control. Therefore, this article proposed a novel synchronous tracking strategy, differential movement synchronous tracking control (DMSTC) strategy, for double-shaking table system while taking the interaction between shaking tables and specimen into consideration. DMSTC Simulink model of the double-shaking table with specimen was established and simulations were conducted in various conditions. The results demonstrate the viability of the proposed DMSTC in that the frequency bandwidth of the double-shaking tables is expanded from 3.27 Hz to 64.57 Hz, the maximum value of differential movement synchronous error is decreased from 1.682 mm to 0.482 mm, and the maximum tracking errors of the two shaking tables decrease from 1.138 mm to 0.044 mm and from 1.030 mm to 0.497 mm, respectively.